Atherosclerosis of the carotid bulb is associated with the severity of orthostatic hypotension in non-diabetic adult patients: a cross-sectional study. (17th February 2019) - Kobayashi, Yusuke; Ishiguro, Hiroaki; Fujikawa, Tetsuya; Kobayashi, Hideo; Sumida, Koichiro; Kagimoto, Minako; Okuyama, Yuki; Ehara, Yosuke; Katsumata, Mari; Fujita, Megumi; Fujiwara, Akira; Saka, Sanae; et al.
ABSTRACT: Background : The carotid bulb has a high density of baroreceptors that play an important role in maintaining blood pressure. We hypothesized that atherosclerosis of the carotid bulb would reflect the severity of orthostatic hypotension more accurately than would atherosclerosis of other carotid artery segments. Methods : This cross-sectional study included 198 non-diabetic adults. We measured the cardio-vascular ankle index as an index of arterial stiffness, intima-media thickness in each carotid artery segment (internal carotid artery, carotid bulb, distal and proximal portions, respectively, of the common carotid artery) as a measure of atherosclerosis, and heart rate variability as a measure of cardiac autonomic function. The sit-to-stand test was used to assess severity of orthostatic hypotension. Results : Intima-media thickness of the carotid bulb was correlated with orthostatic systolic blood pressure change (r = −0.218, p = 0.002), cardio-ankle vascular index (r = 0.365, p < 0.001) and heart rate variability parameters. Multivariate regression analysis revealed that among all of the segments, only intima-media thickness of the carotid bulb was an independent predictor of orthostatic systolic blood pressure change (p = 0.022). Conclusion : Atherosclerosis of the carotid bulb was associated with severity of orthostatic hypotension, arterial stiffening and cardiac autonomic dysfunction than that of other carotid artery segments.